Metrology in health: a pilot study. (16th February 2015) - Ferreira, M; Matos, A
Abstract: The purpose of this paper is to identify and analyze some relevant issues which arise when the concept of metrological traceability is applied to health care facilities. Discussion is structured around the results that were obtained through a characterization and comparative description of the practices applied in 45 different Portuguese health entities. Following a qualitative exploratory approach, the information collected was the support for the initial research hypotheses and the development of the questionnaire survey. It was also applied a quantitative methodology that included a descriptive and inferential statistical analysis of the experimental data set.